S76 Pleuro-parenchymal fibroelastosis: traction bronchiectasis and extent of platythorax on computed tomography are determinants of disease progression and mortality. (December 2018) - Chua, F; George, P; Devaraj, A; Armstrong-James, D; Renzoni, E; Wells, AU; Pulzato, I; Molyneaux, P; Maher, T; Kokosi, M; Kouranos, V; Margaritopoulos, G; et al.
Abstract : Background: Pleuroparenchymal fibroelastosis (PPFE) is an unusual form of idiopathic interstitial pneumonia characterised by the excessive accumulation of elastin-rich fibrotic matrix. Progression of PPFE is dominated by preferential upper lobe lung shrinkage that clinically manifests as platythorax. The pathogenesis of PPFE is poorly understood but idiopathic and secondary forms are recognized, as is an association with opportunistic pulmonary infections. We used computed tomographic and clinico-serological parameters to assess the influence of these factors on the progression and mortality of patients with PPFE. Method: 72 patients (39 female, median age 64) with a multidisciplinary diagnosis of PPFE achieved between March 2012 and January 2018 were identified. CTs were consensus-scored by two thoracic radiologists. The presence of radiological platythorax, denoted by a reduced antero-posterior thoracic diameter and flattening of the anterior chest aspect was shown to be associated with a deep suprasternal notch and/or posterior retraction of the trachea in 45/72 (62%) and 28/72 (39%) patients respectively. Platythorax specifically correlated with both the progression of PPFE on interval cross-sectional imaging (p=0.009) and death (p=0.037). An overtly prominent suprasternal notch on clinical inspection was also present in almost all individuals with CT evidence of platythorax. The presence and severity of traction bronchiectasis within areas of PPFE also correlated with the extent, severity and progression of PPFE (all p<0.05). Pneumothoraces and/or pneumo-mediastinum complicated the clinical course of 9 patients (12.5%). Elevated Aspergillus IgG antibody (>40 mgA/L) was demonstrated in 18/72 (25%) patients. This rate was higher than in reference cohorts of patients with idiopathic pulmonary fibrosis/IPF (20/105; 19%) and chronic hypersensitivity pneumonitis/CHP (12/111; 11%) (p=0.04). Nearly half of all patients (33/72) underwent bronchoalveolar lavage although fungi were not ultimately cultured. Conclusion: Platythorax especially when accompanied by a disctinctly deepened suprasternal notch is a clinico-radiological marker of upper lobe lung volume loss and, more importantly, an index of poor outcome in PPFE. Its manifestation potentially reflects the inexorable physiological decline that often characterises this disease. The possibility that fungal sensitisation may form part of a pathogenetic or progressive PPFE phenotype warrants further investigation.